Harijan Rights and Citizenship In India: Exploring the Dimensions of Caste, Gender, and Poverty in Harijan Rights and Citizenship (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This report develops an understandingon the problem of “Harijan ’ in India. Harijan include a section of  in Indiansociety, who come from the lower castes, particularly the untouchable and otherlower caste, and who beside gender discrimination, also suffered from theprescribed customary provisions in the institution of caste and untouchability.Excluded  are not 'just like' the rest ofthe . They are also disadvantaged by who they are. They suffer fromsocial exclusion which deprives them of choices and opportunities to escapefrom poverty and denies them a voice to claim their rights. There is a closeinter-face between patriarchy and social exclusion which enforce each other.The  from discriminated groups sufferfrom triple deprivation – gender, poverty and social exclusion. The discussionpresented selected evidence on the nature and forms of caste – baseddiscrimination suffered by Harijan  inaccess to sources of livelihood and social needs. This evidence however, isvery limited and there is a need to study the nature and forms ofdiscrimination faced by Harijan  as awoman, as a Harijan woman and as poor . The Harijan woman’s exclusion from therights normally considered as accruing to every Indian citizen thus needs to beexamined more closely, looking both at her conditions of livelihood andemployment and the various ways in which she is subjugated in the public andprivate spheres. The challenge is to capture the interface of these threedimensions of caste, class and gender and to analyse the consequences of socialexclusion and discrimination on their rights and citizenship. This would helpto conceptualize inclusive policies to address the problems of Harijan  more effectively.